Team BFF : race to the finish! - Deutsch, Stacia; Roberts, Christa (New York : Penguin Workshop, 2017)
Sophia and her coding club BFFs are about to participate in their first robot hackathon--a full day of coding robots and meeting other coders--so it's time to step up their game! But when a change of plans threatens to tear their group apart, will Sophie and her friends have each another's backs, or are they destined for an epic fail? They know that coding is all about teamwork and problem solving--maybe friendship is, too!
5.2
3-6
660L
Keywords: Computer programming -- Fiction; Clubs -- Fiction; Schools -- Fiction; Female friendship -- Fiction; Computer programming -- Fiction; Clubs -- Fiction; School stories; Female friendship -- Fiction